Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1016/j.jfda.2014.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Effects of enzymatic extraction on anthocyanins yield of saffron tepals (Crocos sativus) along with its color properties and structural stability

Abstract: An aqueous solution of Pectinex (containing cellulase, hemicellulase, and pectinase) at 1%, 2.5%, 5%, 7%, and 10% concentrations and 40C was used to extract anthocyanins (Acys) of saffron tepals at 20, 40, 60, 120 and 180 min reaction times and compared with ethanol solvent under similar conditions. The Acys of the Pectinex solution reached 6.7 mg/g of tepal powder (∼40% more than the ethanol method) when the enzyme concentrations and extraction times were, respectively, 5% and 60 min. The Acys of aqueous enzy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(26 citation statements)
references
References 34 publications
(38 reference statements)
1
22
2
Order By: Relevance
“…This result stays in accordance with other study where EAE was used for Crocus sativus and it improved by 40% anthocyanins content when compared to a control experiment. Overall, 5% (w/v) of enzyme Pectinex was used, which was produced by Aspergillus aculeatus and contained cellulase, hemicellulase, and pectinase (Lotfi, Hamedi, & Ghorbani, ). Additionally, in other work on the EAE optimization to obtain anthocyanins from Prunus nepalensis , it was demonstrated that the optimal temperature for enzymatic reaction was 40 °C to avoid anthocyanins degradation.…”
Section: Resultsmentioning
confidence: 99%
“…This result stays in accordance with other study where EAE was used for Crocus sativus and it improved by 40% anthocyanins content when compared to a control experiment. Overall, 5% (w/v) of enzyme Pectinex was used, which was produced by Aspergillus aculeatus and contained cellulase, hemicellulase, and pectinase (Lotfi, Hamedi, & Ghorbani, ). Additionally, in other work on the EAE optimization to obtain anthocyanins from Prunus nepalensis , it was demonstrated that the optimal temperature for enzymatic reaction was 40 °C to avoid anthocyanins degradation.…”
Section: Resultsmentioning
confidence: 99%
“…Enzyme concentration, composition, particle size, water-to-solid ratio and hydrolysis time are some of the major factors that influence the enzyme-assisted extraction of various bioactive compounds (Puri et al 2012). This technique has been explored for the extraction of various components, such as carotenoids from pumpkin (Ghosh and Biswas 2015), anthocyanins from crocus sativus (Lotfi et al 2015) and anthocyanin from grape skin. (Muñoz et al 2004).…”
Section: Enzyme-assisted Extractionmentioning
confidence: 99%
“…The enzyme concentration was chosen according to published reports on the influence of Cellubrix (mixture of cellulase and cellobiase) pre-treatment on anthocyanins recovery from other flowers. 13 After incubation for different times, the enzymes were inactivated at 100 °C for 5 min and extraction was further performed by the optimal UAE. Control samples (without enzymatic pre-treatment) were maintained in buffer solution under similar conditions (time, t) and further processed by ultrasonication.…”
Section: Extraction Proceduresmentioning
confidence: 99%